DETERMINAN INISIASI MENYUSU DINI (IMD) WANITA USIA 15-49 TAHUN DI INDONESIA (ANALISIS DATA SDKI 2012) - Nur Aini; Budyanra Budyanra; Indonesian Journal of Statistics; Its Applications IJSA (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2019)
Early Breastfeeding Initiation (EBI) is one of the most effective ways to reduce neonatal mortality in Indonesia. Implementation of EBI in Indonesia in 2012 is still in the